Probing electronic structures of graphene under magnetic field and electric field by Raman spectroscopy - Shen, Xiaonan (2015)
This thesis presents research in frontiers of Raman spectroscopy: the magneto-Raman scattering of monolayer graphene on graphite and electrical field tuning of magneto-phonon resonance (MPR) in graphene transistor.